Transport Phenomena Induced by the Energy Pulse in a Crystal - Pogorelov, A.E. (Металлофизика и новейшие технологии, 2014)
The phenomenon of rapid mass-transfer in solid state observed in metals after pulsed action is characterized by transfer of atoms within the short periods of action time to the depths significantly exceeding the diffusion depth under the conditions of stationary annealing. The features of other transport phenomena (mass-transfer, heat-transfer, etc.) arising in metal at pulsed energy action on a crystal are also discussed. The best instrument to study transformations in the matter under pulsed action is an easily controlled laser pulse. In a given work, the nature and correlations between transport phenomena in metals excited by the energy pulse are studied.